2022
DOI: 10.1073/pnas.2202821119
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation promotes cerebellum development and medulloblastoma oncogenesis via SHH signaling

Abstract: Sonic hedgehog (Shh) signaling plays a critical role in regulating cerebellum development by maintaining the physiological proliferation of granule neuron precursors (GNPs), and its dysregulation leads to the oncogenesis of medulloblastoma. O-GlcNAcylation (O-GlcNAc) of proteins is an emerging regulator of brain function that maintains normal development and neuronal circuitry. Here, we demonstrate that O-GlcNAc transferase (OGT) in GNPs mediate the cerebellum development, and the progression of the Shh subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…The presence of this PTM on diverse proteins is consistent with its emergence as a regulator of numerous cellular pathways ranging from transcription [1] and translation [2, 3] through to participating in cell signaling [4, 5] . Given these molecular roles, it is unsurprising that O‐GlcNAc is implicated in a range of physiological processes ranging, for example, from stress response [6] to nutrient sensing [4, 7] . Remarkably, the modification of proteins with O‐GlcNAc is principally controlled by just two enzymes.…”
Section: Introductionmentioning
confidence: 73%
“…The presence of this PTM on diverse proteins is consistent with its emergence as a regulator of numerous cellular pathways ranging from transcription [1] and translation [2, 3] through to participating in cell signaling [4, 5] . Given these molecular roles, it is unsurprising that O‐GlcNAc is implicated in a range of physiological processes ranging, for example, from stress response [6] to nutrient sensing [4, 7] . Remarkably, the modification of proteins with O‐GlcNAc is principally controlled by just two enzymes.…”
Section: Introductionmentioning
confidence: 73%
“…To test whether decreasing O-GlcNAc in aged mice can restore spermatogenesis, we used the enzymatic OGT inhibitor OSMI-1, which was previously reported to be suitable for long-term use without side effects in a mouse model (25). After intraperitoneal administration of 10 mg/kg OSMI-1 in aged mice for 35 consecutive days (Fig.…”
Section: 7mentioning
confidence: 99%
“…Specifically, elevated OGT in GBM cells increases the phosphorylation of ACSS2 at Ser267 in a CDK5-dependent manner, thereby reducing polyubiquitination and degradation to increase its stability. Chen et al (Chen et al 2022 ) observed the elevated O -GlcNAc levels in human samples of Sonic hedgehog (Shh)-subtype medulloblastoma and revealed that OGT in granule neuron precursors (GNPs) may contribute to medulloblastoma oncogenesis by activating the Shh signaling pathway via O -GlcNAcylation at S355 of GLI family zinc finger 2 (Gli2). These studies reveal the important role of O -GlcNAc signaling in brain cancer and deserve further exploration.…”
Section: O -Glcnac and Cancermentioning
confidence: 99%